Pengaruh Penggunaan Aplikasi Wattpad Terhadap Kemampuan Menulis Cerita Pendek - Najwa Salsabila; Putri Nayla Syefira; Feirhat Muhammad Fatah; Tatu Hilaliyah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Every human being is gifted with the ability to write, writing skills still need to be developed so that a person's writing ability continues to improve. Like students, students' writing skills are still very lacking. Therefore, it needs to be trained continuously. This research aims to describe the influence of using the Wattpad application on the ability to write short stories of Indonesian language education students class of 2021. This research is a type of quantitative research. The method used is an experimental method with a One-Group Pretest-Posttest design. The number of samples in this study was 25 people. This research was carried out on Indonesian Language Education (PBI) students class of 2021, specifically in class B. The results of the research showed that the average pretest was 72.04 and the average final test (posttest) was 94.30. This shows that the class of 2021 Indonesian language education students experienced improvement after implementing the Wattpad application in their ability to write short stories.